2012
DOI: 10.1044/ffd22.2.51
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of a Stuttering Disorder on Western Australian Children and Adolescents

Abstract: In this study, we examined the impact of a stuttering disorder on children (n=50) and adolescents (n=45) living in Western Australia. We compared the reactions and experiences of children and adolescents who stutter to children and adolescents who do not stutter. We compared the participants who stuttered and the fluent participants using adapted versions of the Overall Assessment of the Speaker’s Experience of Stuttering (OASES). We also examined the relationship between biopsychosocial impact and stuttered s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 37 publications
2
24
0
Order By: Relevance
“…Research to date has shown that stuttering during adolescence has the potential to negatively impact communication attitudes, life satisfaction, quality of life, self-esteem, and psychosocial functioning (Beilby et al, 2012;Blood & Blood, 2004;Blood et al, 2011;Erickson & Block, 2013;Van Borsel et al, 2011). Although research evidence to date remains inconclusive, several studies have shown that adolescents who stutter may report heightened anxiety, negative attitudes to communication, negative peer experiences, and low self-esteem (Blood et al, 2001;Blood et al, 2004Blood et al, , 2011Mulcahy et al, 2008;Smith et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Research to date has shown that stuttering during adolescence has the potential to negatively impact communication attitudes, life satisfaction, quality of life, self-esteem, and psychosocial functioning (Beilby et al, 2012;Blood & Blood, 2004;Blood et al, 2011;Erickson & Block, 2013;Van Borsel et al, 2011). Although research evidence to date remains inconclusive, several studies have shown that adolescents who stutter may report heightened anxiety, negative attitudes to communication, negative peer experiences, and low self-esteem (Blood et al, 2001;Blood et al, 2004Blood et al, , 2011Mulcahy et al, 2008;Smith et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In this view, treatment plans should include multiple goals that can be selected for each individual's unique needs. Moreover, the level of fluency (or stuttering) a person exhibits may be only moderately related-or even unrelatedto the adverse impact he or she experiences (e.g., Beilby, Byrnes, & Yaruss, 2012;Blumgart, Tran, Yaruss, & Craig, 2012;Koedoot, Versteegh, & Yaruss, 2011). Thus, a more comprehensive approach to treatment might address increased fluency as well as other goals.…”
Section: The Goals Of Stuttering Treatment: Acceptance Versus Fluencymentioning
confidence: 99%
“…The ability of an individual who stutters to communicate effectively in a variety of every day speaking situations is not necessarily determined by the amount of stuttering they experience (Beilby, Byrnes & Yaruss, 2012;Blumgart, Tran, Yaruss & Craig, 2012;Koedoot, Versteegh, Yaruss, 2011;Mulcahy, Hennessey, Beilby, & Byrnes, 2008). It is affected by how completely the person is able to convey their spoken message in each situation.…”
Section: Psychosocial Impact Of Stutteringmentioning
confidence: 97%